Evaluation of the Making WAVES project in Liverpool, England: improving support for intimidated witnesses. (1st March 2011) - Quigg, Z; Warren, I; Hungerford, D; Hughes, K; Furness, L
Abstract : Background: Witness intimidation can have devastating effects on the well being of victims, their families and communities, and can prevent crime reporting, including violence. In Liverpool (North West England), the Making WAVES pilot project aimed to encourage intimidated witnesses to report crime and to support them throughout the criminal justice system more effectively. This paper discusses the evaluation of the Making WAVES project. Methods: A process and outcome evaluation was undertaken. Project implementation, limitations and areas for improvement were examined. The evaluation assessed the impact of the project on: levels of support to intimidated witnesses, crime reporting and levels of witness intimidation. Methods included: a pre- and postpilot community wide survey; community focus groups; interviews with project staff, key stakeholders and project users; and analyses of project and local partner data. Results: Over 12 months, 155 cases were supported through the project, representing 353 intimidated witnesses. Findings suggest that the project has led to improvements in reporting of crime and multi-agency support for victims. Significant reductions in levels of intimidation experienced in the local community were seen (55% to 22%; p<0.01). A project coordinator, a neutral location to report crimes and access support, and a multi-agency project steering group, were identified as areas of good practice. Discussion: The evidence from this evaluation points to the positive impact of the Making WAVES project. As a result Making WAVES has now been implemented in four other areas of Liverpool, and is promoted nationally as best practice.